2010
DOI: 10.1590/s1677-55382010000500011
|View full text |Cite
|
Sign up to set email alerts
|

The position of the testis during the fetal period: an additional parameter to estimate fetal weight

Abstract: Purpose: To establish a correlation between testicular position and fetal weight, in order to provide an additional prenatal parameter for fetal weight estimation. Materials and Methods:We studied 288 testes from 144 human fetuses. The fetuses were assessed as regards weight, total length, crown-rump length and foot length. Fetal age was calculated according to the foot length criteria. The position of the testis was classified as abdominal, inguinal or scrotal. Results: One hundred and ninety seven testes (68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Studies correlating fetal parameters with testicular migration during human fetal period are rare in literature. A previous study of fetal weight and testicular descent in human fetuses showed that almost 7% of the testes in fetuses with weight up to 500g had the testes positioned in the inguinal canal ( 26 ). In our sample, we observed that the distance between the kidney and the testis was greater in fetuses weighing more than 350g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies correlating fetal parameters with testicular migration during human fetal period are rare in literature. A previous study of fetal weight and testicular descent in human fetuses showed that almost 7% of the testes in fetuses with weight up to 500g had the testes positioned in the inguinal canal ( 26 ). In our sample, we observed that the distance between the kidney and the testis was greater in fetuses weighing more than 350g.…”
Section: Discussionmentioning
confidence: 99%